Exploring the perceived challenges of single mothers with children diagnosed with autism disorder in the junior phase at Vera School - Monare, Nthabiseng (Department of Social Development, 2016)
This study aimed to explore the perceived challenges of single mothers with children diagnosed with Autism who are in the junior phase at Vera School, focussing on key struggles which they face in caring for their children. Emphasis was on parental stresses during their children's diagnostic processes as well as lack of availability and accessibility of resources about Autism Spectrum Disorder. A qualitative research design was used to carry out the research, and purposive sampling was utilised to select the sample for this study. The sample comprised of 15 single mothers. A semi-structured interview schedule and a voice recorder were used to conduct the interviews. The research was conducted at Vera School, Rondebosch in Cape Town. Findings were drawn from the responses of the participants and compared with literature from previous studies. These findings indicated that single mothers of children diagnosed with Autism lack support to cope with the demands of caring for their children. This was highlighted in the early stages of assessment, making a diagnosis, and during early intervention of their children in a special needs school. Multiple roles, financial constraints and stigma were primary sources of parental stress, as pointed out in this study. Limited resources such as long waiting lists for admissions at special schools and aftercare facilities were highlighted as a great need.